Aware I Am Alone: Intersections of Solitude and Mindfulness - Richard Cleveland (Nicolaus Copernicus University in Toruń, 2020)
This paper explores the relationship between solitude and mindfulness. Parallels between the two constructs exist, allowing them to complement each other in furthering the well-being of individuals and communities. Three perspectives through which mindfulness may assist in forming foundational understandings of solitude are presented; these comprise Theoretical, Practice, and Research. The Theoretical lens provides introductory understandings of both solitude and mindfulness. On this basis, integral parallels between the two constructs are outlined. Next, Practice reviews solitude that is fostered through mindfulness practices. Further, additional models for recognising solitude as a part of mindfulness are proposed. Finally, Research summarises a current project that uses biophysical data to investigate mindfulness experienced both alone and together.